Pengaruh Strategi Pembelajaran terhadap Hasil Belajar Keterampilan Groundstrokes Tenis Mahasiswa - Hariyoko Hariyoko (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
The Effect of Learning Strategies on Students' Groundstrokes Skills at Playing Tennis. The study aimed to investigate the effect of learning strategies on students' groundstrokes skills at playing tennis. Randomized group design was employed to select the 32 students among 100 students of Physical Education Department, Faculty of Education IKIP Malang. Hypotheses were tested using Anova. The findings suggest that the effect of varied learning strategies on students' groundstrokes skills was significantly different from that of conventional ones.